Mutlak bozma nedeni olarak savunma hakkının kısıtlanması - Dereli, Alparslan (My University, 2019)
Tezimizin konusunu “Mutlak Bozma Nedeni Olarak Savunma Hakkının Kısıtlanması” oluşturmaktadır. Savunma hakkının kısıtlanmasının mutlak bozma nedeni şeklinde düzenlenmesi 5271 sayılı Ceza Muhakemesi Kanunu’nun 289. maddesinin 1. fıkrasının (h) bendinde düzenlenmiştir.Tarihi süreçte ceza yargılamalarında savunma hakkı dönem dönem önemli bir yere sahipken, dönem dönem maddi gerçeğe ulaşma gayesinin herşeyden üstün tutulması sebebiyle göz ardı edilmiştir. Günümüzde İnsan Hakları Avrupa Sözleşmesi’nde ve Ceza Muhakemesi Kanunu’nda yer alan birçok düzenlemeyle savunma hakkının ihlal edilmesinin önüne geçilmesi amaçlanmıştır. Çalışmamız iki bölümden oluşmaktadır. Birinci bölümde savunma hakkı kavramına, savunma hakkının tarihi gelişimine ve bu hakla ilişkili ceza yargılaması ilkelerine değinilmiştir. İkinci bölümde ise savunma hakkının kısıtlanmasının kanun yolu denetimi ele alınmış ve Türk hukukunda savunma hakkının kısıtlanmasının mutlak bozma nedeni sayıldığı önemli durumlar Yargıtay kararları ışığında detaylı olarak incelenmiştir.

The topic of this thesis is “The Restriction of the Right to Defense as Cause of Absolute for Reverse. The restriction of the right to defense is regulated as the reason of absolute distortion in the 5271 numbered Code of Criminal Procedure, specifically first paragraph of Article 289. clause in h sub-clause.In legal history, while the right to defense in criminal proceedings was highly important, sometimes the object of reaching the material truth was overlooked because it was above all. Nowadays, it is aimed to prevent violations of the right to defense by many regulations in the European Convention on Human Rights and the Code of Criminal Procedure. This study consists of two parts. In the first part, the concept of the right to defense, the historical development of the right to defense and the principles of criminal proceedings related to this right are addressed. In the second part, the legal way control of the restriction of the right to defense taken into consideration and the important cases where the restriction of the right to defense in Turkish Law was considered as the absolute cause of destruction were examined in detail in the light of the decisions of the Court of Cassation.
Keywords: Absolute Ground for a Reverse; Adil yargılama; Adil Yargılanma Hakkı; Fair Trial; Fairness; Hukuk; Law; Mutlak Bozma Nedeni; Restriction of Right to Defense; Right of Defense; Savunma Hakkı; Savunma Hakkının Kısıtlanması